Question
upstudy study bank question image url

Simplify: \( \left[\frac{3^{x+1}+12.3^{x-1}}{7.9^{x}}\right]^{\frac{1}{x}} \)

Ask by Bartlett Kelley. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The simplified expression is \( \frac{1}{3} \).

Solution

We start with the expression   [ (3^(x+1) + 12·3^(x–1)) / (7·9^x) ]^(1/x). Note: The dot “·” represents multiplication. That is, 12·3^(x–1) means 12 times 3^(x–1) and 7·9^x means 7 times 9^x. Step 1. Rewrite Numerator Write 3^(x+1) as 3^(x–1)·3^2 (since 3^(x+1) = 3^(x–1)·3^2). Then the numerator becomes:   3^(x–1)·3^2 + 12·3^(x–1)   = 3^(x–1)·(9 + 12)   = 3^(x–1)·21. Step 2. Rewrite Denominator Express 9^x as (3^2)^x = 3^(2x). So the denominator becomes:   7·9^x = 7·3^(2x). Step 3. Combine and simplify the fraction Our expression inside the bracket now is:   [21·3^(x–1)] / [7·3^(2x)]. Divide the constant coefficients:   21 / 7 = 3. Now, handle the powers of 3 by subtracting exponents:   3^(x–1) / 3^(2x) = 3^[(x–1) – 2x] = 3^(–x – 1). So the simplified fraction is:   3 · 3^(–x – 1). Combine the powers (recall 3 = 3^1):   3^1 · 3^(–x – 1) = 3^(1 – x – 1) = 3^(–x). Thus, the expression inside the bracket becomes 3^(–x). Step 4. Apply the exponent 1/x Now take the 1/x-th power of the expression:   [3^(–x)]^(1/x) = 3^(–x/x) = 3^(–1). Step 5. Write the Final Answer 3^(–1) equals 1/3. Therefore, the simplified expression is 1/3.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To simplify the expression \( \left[\frac{3^{x+1}+12 \cdot 3^{x-1}}{7 \cdot 9^{x}}\right]^{\frac{1}{x}} \), we will start by simplifying the numerator and the denominator separately. First, let's simplify the numerator: \[ 3^{x+1} + 12 \cdot 3^{x-1} \] We can factor out \(3^{x-1}\) from both terms: \[ = 3^{x-1}(3^2 + 12) \] \[ = 3^{x-1}(9 + 12) = 3^{x-1}(21) = 21 \cdot 3^{x-1} \] Now, let’s simplify the denominator: \[ 7 \cdot 9^{x} = 7 \cdot (3^2)^x = 7 \cdot 3^{2x} \] Now substitute back into the expression: \[ \frac{3^{x+1} + 12 \cdot 3^{x-1}}{7 \cdot 9^{x}} = \frac{21 \cdot 3^{x-1}}{7 \cdot 3^{2x}} = \frac{21}{7} \cdot \frac{3^{x-1}}{3^{2x}} = 3 \cdot 3^{x-1 - 2x} = 3 \cdot 3^{-x - 1} = \frac{3}{3^{x+1}} = \frac{1}{3^x} \] Now we have: \[ \left[\frac{1}{3^x}\right]^{\frac{1}{x}} = (3^{-x})^{\frac{1}{x}} = 3^{-1} = \frac{1}{3} \] Thus, the simplified expression is: \[ \boxed{\frac{1}{3}} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy